Material Mechanics and Hussein Zbib: A Tribute to His Memory - Aifantis, Elias C. (Journal of Engineering Materials and Technology-Transactions of the Asme, 2022)
A number of new trends in material mechanics and engineering science can be traced back to the PhD work of Hussein Zbib at Michigan Technological University (MTU). In particular, the topics of shear bands and plastic instabilities found a new basis and direction, prompting distinguished researchers—whom he begun interacting with during his doctoral and post-doctoral years (see Appendix)—to turn their attention to gradient plasticity and make their own monumental contributions in this field. This article first provides a brief account of the initial attempts, I had the joy to share with him, on gradient mechanics theory and its implications to the problems of strain localization and size effects. It then continues with a brief exposition of topics that his “scientific family” has taken up in parallel with him or later on. Finally, it concludes with a sketch of ideas I discussed with him during his post-doctoral period at MTU and his tenure period as a faculty member and Chairman at Washington State University (WSU) which, unfortunately, he did not have the time to elaborate upon.
CRIS-Team Scopus Importer:2022-04-15
Keywords: adiabatic; gradient plasticity; localization/post-localization and size effects; plastic spin and rotational bands; Portevin-Le Châtelier bands; shear banding